Creatine kinase is associated with reduced inflammation in a general population: The Tromsø study - Bekkelund, Svein Ivar; Johnsen, Stein Harald (PLOS ONE, 2018)
The following article, Bekkelund, S.I. & Johnsen, S.H. (2018). Creatine kinase is associated with reduced inflammation in a general population: The Tromsø study. PLoS ONE, 13 (5), can be accessed at https://doi.org/10.1371/journal.pone.0198133 . Background : Creatine kinase (CK) has been associated with reduced inflammation in obesity while inflammation is associated with obesity-related cardiovascular diseases. We investigated the relationship between CK and high sensitive C-reactive protein (hs-CRP) in a general population. Methods : CK and hs-CRP were measured in the population-based Tromsø study that included entire birth cohorts and random samples of citizens between 30–87 years of age. The analyses were performed sex-stratified in 5969 men and 6827 women. Results : CK correlated negatively with hs-CRP in men (r = -0.08, P <0.001) and women (r = -0.06, P <0.001). In univariable regression analyses, CK associated negatively with hs-CRP in men (ß = -0.14, 95% CI -0.19 to -0.10, P <0.001) and women (ß = -0.13, 95% CI -0.18 to -0.08, P <0.001). Mean CK declined from the 2. to the 4. quartiles of hs-CRP in both genders (P <0.001 for trends). There were positive correlations between CK and body mass index (BMI) in men (r = 0.10, P <0.001) and women (r = 0.07, P <0.001). Multiple regression analyses showed a 0.13 unit decrease in hs-CRP (mg/dl) per unit CK increase in men (95% CI -0.35 to -0.20) and 0.29 mg/dl in women (95% CI -0.36 to -0.21) when adjusted for age, BMI, lipids, s-glucose, s-creatinine, transaminases and coronary heart disease. Conclusion : CK were inversely and independently associated with hs-CRP in a general population. These data provide evidence that CK might have anti-inflammatory properties, but the mechanism and clinical implications are unclarified.